A dual-clam species 63 K SNP array for sustainable production and conservation of wild resources - Marialaura Gallo; Massimiliano Babbucci; Sergio Fernández Boo; Tim Bean; Giulia Dalla Rovere; Morgan Smits; Carolina Peñaloza; Ross Houston; Shernae Woolley; Francesco Cicala; Rafaella Franch; Serena Ferraresso; et al. (Aquaculture, 2026)

Towards new horizons in shrimp cell culture: A streamlined protocol for culturing healthy, enduring haemocytes and lymphoid organ cells from Pacific whiteleg shrimp (Litopenaeus vannamei) - Alexandra Florea; Sarah Ho; Joe Mee; Ross Houston; Diego Robledo; Tim P. Bean (Aquaculture, 2026)

Geographic origin and post-invasion genetic divergence of Mytilus galloprovincialis in China - Jian'an Li; Ben Yang; Ahmed Mokrani; Mengmeng Xu; Xiaojie Han; Tim P. Bean; Robert P. Ellis; Shikai Liu (Marine Pollution Bulletin, 2026)

Non-invasive detection method for Bonamia ostreae infected Ostrea edulis - Tim Regan; Lavanya Vythalingam; Jennifer Nascimento-Schulze; Owen Paisley; Alain Karmitz; Nuala M. Hanley; William G. Sanderson; Tim P. Bean (Aquaculture, 2025)

High-density linkage map and single nucleotide polymorphism association with whole weight, meat yield, and shell shape in the Portuguese oyster, Crassostrea angulata - Sang Van Vu; Manoharan Kumar; Pasi Rastas; Pierre Boudry; Almas Gheyas; Tim P. Bean; Mai Thi Nguyen; Khanh Dang Tran; Juergen Geist; Hoang Huy Nguyen; Wayne O’Connor; Ha Luu Ngoc Tran; et al. (Aquaculture International, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Optimizing hatchery practices for genetic improvement of marine bivalves - Jennifer C. Nascimento‐Schulze; Tim P. Bean; Ross D. Houston; Eduarda M. Santos; Matthew B. Sanders; Ceri Lewis; Robert P. Ellis (Reviews in Aquaculture, 2021)
Aquaculture currently accounts for approximately half of all seafood produced and is the fastest growing farmed food sector globally. Marine bivalve aquaculture, the farming of oysters, mussels and clams, represents a highly sustainable component of this industry and has major potential for global expansion via increased efficiency, and numbers of, production systems. Artificial spat propagation (i.e. settled juveniles) in hatcheries and selective breeding have the potential to offer rapid and widespread gains for molluscan aquaculture industry. However, bivalves have unique life‐histories, genetic and genomic characteristics, which present significant challenges to achieving such genetic improvement. Selection pressures experienced by bivalve larvae and spat in the wild contribute to drive population structure and animal fitness. Similarly, domestication selection is likely to act on hatchery‐produced spat, the full implications of which have not been fully explored. In this review, we outline the key features of these taxa and production practices applied in bivalve aquaculture, which have the potential to affect the genetic and phenotypic variability of hatchery‐propagated stock. Alongside, we compare artificial and natural processes experienced by bivalves to investigate the possible consequences of hatchery propagation on stock production. In addition, we identify key areas of investigation that need to be prioritized to continue to the advancement of bivalve genetic improvement via selective breeding. The growing accessibility of next‐generation sequencing technology and high‐powered computational capabilities facilitate the implementation of novel genomic tools in breeding programmes of aquatic species. These emerging techniques represent an exciting opportunity for sustainably expanding the bivalve aquaculture sector.

Genetic improvement technologies to support the sustainable growth of UK aquaculture - Tim Regan; Tim P. Bean; Tim Ellis; Andrew Davie; Stefano Carboni; Herve Migaud; Ross D. Houston (Reviews in Aquaculture, 2021)
While the UK is the fourth largest aquaculture producer in Europe by volume, it is the second largest by value with an annual first sale value of around £1 billion. Over 90% of this value is from Atlantic salmon farmed in Scotland, but other finfish and shellfish aquaculture species are important to several UK regions. In this review, we describe the state of the art in UK aquaculture breeding and stock supply, and how innovation in genetics technologies can help achieve the Scottish Government’s ambitious target of doubling its aquaculture industry by 2030. Particular attention is given to the four most important UK aquaculture species: Atlantic salmon, rainbow trout, blue mussel and Pacific oyster, and we contrast the highly variable level of selective breeding and genomics technologies used in these sectors. A major factor in the success of Atlantic salmon farming has been large‐scale investment in modern breeding programmes, including family selection programmes and genomic selection. This has proven cost‐effective at scale, leading to improved production efficiency and reduction of some infectious diseases. We discuss the feasibility of applying similar technologies to the UK shellfish sectors, to ensure consistent and robust spat supply and begin trait selection. Furthermore, we discuss species‐specific application of modern breeding technologies in a global context, and the future potential of genomics and genome editing technologies to improve commercially desirable traits. Increased adoption of modern breeding technologies will assist UK aquaculture industries to meet the challenges for sustainable expansion, and remain competitive in a global market.

Horizon scanning for invasive alien species with the potential to threaten biodiversity and human health on a Mediterranean island - Jodey Peyton; Angeliki F. Martinou; Oliver L. Pescott; Monica Demetriou; Tim Adriaens; Margarita Arianoutsou; Ioannis Bazos; Colin W. Bean; Olaf Booy; Marc Botham; J. Robert Britton; Javier Lobon Cervia; et al. (Biological Invasions, 2019)

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)